The Comparison of Stress Coping Styles in Athletes and Non-Athletes with High and Low Self-Esteem - Mahmood Sheikh; javad Afshari (University of Tehran, 2012)
The aim of this study was to investigate differences in stress coping styles between athletic and non-athletic students with high and low self-esteem. For this purpose, 465 students (118 females and 347 males, mean age 23.58+3.20 years) were selected by available sampling method. The questionnaire of coping styles (Dadsetan et al. 1384) and self-esteem (Rosenberg, 1987) were used to evaluate the variables of coping styles and self-esteem. The collected data were analyzed through descriptive statistics and MANOVA statistical models. The findings showed a significant difference in sport condition among coping styles. Also, a significant difference existed in self-esteem levels among coping styles. There was a significant interaction between sport condition and self-esteem in these coping styles. The findings showed that non-athletes with low self-esteem, non-athletes with high self-esteem, athletes with low self-esteem and athletes with high self-esteem respectively used lowest to highest level of active coping style. There was an interaction between physical activity level and self-esteem level in inflexible coping styles. Non-athletes used this coping style almost to the same extent. Athletes with high self-esteem and athletes with low self-esteem respectively used this coping style more than other groups.